Finite element analysis of bone-implant biomechanics: Refinement through featuring various osseointegration conditions - Kurniawan, Denni; Nor, F.; Lee, H.; Lim, J. (Elsevier, 2012)
A refinement technique is proposed for developing finite element models capable of simulating peri-implant bone conditions for bone types II, III, and IV at various degrees of osseointegration. The refined models feature a transition region between bone (cortical and cancellous) and implant and designate it partially to fully osseointegrated by assigning corresponding fractions of the bulk bone's elastic properties to this region. Bone is assumed to be transversely isotropic. The refined technique is implemented in a case study, in which osseointegrated (25-100%) peri-implant bone, type II, III, or IV with an implant attached, is loaded with a 100 MPa occlusal load. The biomechanics of this peri-implant bone was simulated and analysed. Results showed that the less dense bone must support higher stress and strain, especially at the cortical region. Higher degree of osseointegration induced higher stress but lower strain. Both the bone type and the osseointegration condition significantly affected the stress-strain relation. For minimum stress and strain, denser and more osseointegrated peri-implant bone is desirable. When bone failure criteria were set, based on the yield strength and strain of the bone, a higher degree of osseointegration was needed for the less dense peri-implant bone to be considered safe. © 2011 International Association of Oral and Maxillofacial Surgeons.